Crecimiento, productividad y cambio tecnológico en el sector agropecuario: Alguna evidencia para la economía argentina, 1985-2018 - Luis N. Lanteri (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2019)
– In this paper, we calculated the growth rates of total factor productivity (TFP), corresponding to the argentine agricultural sector, according to the neoclassical theory of growth (period 1985- 2018). In turn, we estimated a translogarithmic cost function, with four factors of production (land, capital, labor and fertilizer consumption), in order to compute the Allen-Uzawa partial elasticities of substitution between the factors and the bias of technological change followed in the sector, during the same period. This system of simultaneous equations is estimated through the SUR method developed by Zellner. The results found do not allow us to be so conclusive regarding the validity of the theory of induced innovation, for argentine agriculture.
Keywords: C51; O47; Q10; 330; agricultural sector; productivity; translogarithmic cost function; technological bias; theory of induced innovation